2008
DOI: 10.1111/j.1095-8649.2007.01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic polymorphism in brook charr revealed by diet, parasites and morphometrics

Abstract: Stomach contents, parasite assemblages and morphometrics were compared in brook charr Salvelinus fontinalis from the littoral and pelagic zone of two adjacent lakes on the Canadian Shield. In lac Baie des OnzeÎles, fish from the littoral zone had greater abundance of benthic prey in their stomach and were more heavily infected by parasites that use intermediate hosts associated with the littoral zone than fish captured in the pelagic zone. Littoral and pelagic brook charr from this lake also differed in regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 50 publications
4
44
0
Order By: Relevance
“…In the presence of northern pike, Esox lucius, predatorinduced changes in body shape of crucian carp, Carassius carassius provide a shrinking example of adaptive plasticity by developing a deeper body (Bronmark and Miner 1992). Adaptive plasticity may also contribute to the morphological differences between the benthic and limnetic forms observed in a variety of fish taxa (Robinson and Wilson 1994;Robinson and Parsons 2002;Sacotte and Magnan 2006;Knudsen et al 2007;Bertrand et al 2008). The limnetic forms have more and longer gill rakers; shallower bodies and heads; longer heads, snouts, and upper jaws; and larger eyes than the benthic forms (McPhail 1984(McPhail , 1992.…”
Section: Environmental Influencesmentioning
confidence: 95%
“…In the presence of northern pike, Esox lucius, predatorinduced changes in body shape of crucian carp, Carassius carassius provide a shrinking example of adaptive plasticity by developing a deeper body (Bronmark and Miner 1992). Adaptive plasticity may also contribute to the morphological differences between the benthic and limnetic forms observed in a variety of fish taxa (Robinson and Wilson 1994;Robinson and Parsons 2002;Sacotte and Magnan 2006;Knudsen et al 2007;Bertrand et al 2008). The limnetic forms have more and longer gill rakers; shallower bodies and heads; longer heads, snouts, and upper jaws; and larger eyes than the benthic forms (McPhail 1984(McPhail , 1992.…”
Section: Environmental Influencesmentioning
confidence: 95%
“…Of particular interest was the fascinating number of sympatric forms of S. alpinus from Lake Tinnsjøen in Norway (four, as in Lake Thingvallavatn in Iceland), with an exotic profundal form found at 450 m depth that parallels that reported in Gander Lake, Newfoundland, (O'Connell et al, 2005). Additional studies of intraspecific variation in Brook charr (Bertrand et al, 2008;Samways et al, 2015), Dolly Varden (Oleinik & Skurikhinal, 2010), and Lake charr (Eshenroder, 2008;Chavarie et al, 2016) have similarly demonstrated the high degree of polymorphism observed in Arctic charr, such that one can conclude it to be characteristic of the genus Salvelinus.…”
Section: Evolutionary Studiesmentioning
confidence: 87%
“…Parasites were a more signiWcant predictor of the trophic position and stable isotope ratio of yellow perch (Perca Xavescens) in Canadian Shield lakes compared to gut contents (Johnson et al 2004). In a parallel study, parasites could predict the trophic position of brook charr (Salvelinus fontinalis) better than observed diet or morphometrics in Quebec lakes Table 2 ( Bertrand et al 2008). Thus, parasites are indeed eVective information units with which trophic relationships can be constructed (Marcogliese 2003(Marcogliese , 2004(Marcogliese , 2005.…”
Section: Discussionmentioning
confidence: 97%